ORGANIZATION OF PROGRESS AND ATTENDANCE TRACKING IN THE MOODLE LEARNING MANAGEMENT SYSTEM (Journal of Information Technologies in Education (ITE), 2015)
The article considers usage of Moodle learning management system for current progress and attendance tracking of full time students. Evaluation systems, which are used in universities of Ukraine, are analyzed. Their basis in most cases is point accumulation system, which is useful for manual calculation of final grades at the end of the semester, but it is not useful for comparison of current students’ achievements at different subjects or achievements at any time during the semester. Also this system is not useful for putting current grades, because teaches often have to use unusual grade scales which are different from 5-point system. Because of that it is proposed to use mathematically equivalent weighted average grade, which allows to avoid mentioned disadvantages. Questions of implementation of proposed system are considered by means of gradebook of Moodle learning management system. Attendance accounting module is considered and method of using subcourse module for attendance and grades shared data import in course gradebook, where student’s rating is calculated for all disciplines is proposed.
Keywords: evaluation system; Moodle; the organization progress and attendance records